Ecological aspiration and the income of farmers aroused by Grain for Green Project - Chen, Shengdong; Duan, Pei; Yu, Xiaoying (Frontiers in Ecology and Evolution, 2022)
The more fragile the ecology, the stronger the farmers' awareness of environmental protection. China's Grain to Green Project policy-returning farmland to forests (GGP), as an external shock, has sparked people's ecological aspirations. Everyone has noticed the phenomenon of ecosystem degradation and overlapping poverty. It aims to analyze the environmental and income changes brought about by GGP and considers farmers' self-selection problems but lacks their subjective initiative thinking. Our study aims to fill this gap by assessing the dominance of farmers' ecological aspirations in ecologically vulnerable areas of a forest grass model in Xinjiang, China. It is based on the aspiration theory and the theoretical model of the economic impact of ecological aspiration on the GGP in China. Results show that farmers' ecological aspirations can increase their enthusiasm to participate in the GGP. Under counterfactual conditions, participation in the GGP reduces farmers' total income to a certain extent. But in the long run, the intermediary effect is used to analyze the economic effect of ecological aspiration on returning farmland to forest. It is found that farmers' ecological aspiration affects household income by influencing income expectation. Our findings have essential practical implications and provide an important reference for consolidating the achievements of poverty alleviation and the effective promotion of rural revitalization. In addition, it also provides a way to achieve the goal of carbon peak and carbon neutrality for building environmentally friendly regions.